2016
DOI: 10.1038/srep24121
|View full text |Cite
|
Sign up to set email alerts
|

C7 genotype of the donor may predict early bacterial infection after liver transplantation

Abstract: Post-transplantation infection causes high mortality and remains a significant challenge. High clinical risk factors for bacterial infection in recipients are often found in critically ill patients. However, for some recipients, bacterial infections are inevitable. It is conceivable that this susceptibility may be related to the genetics of the donor and recipient. Using expression quantitative trait loci (eQTL) analysis, we found that the C7 rs6876739 CC genotypes and mannan-binding lectin (MBL2) gene polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…After removing of duplicate studies and detailed evaluation of titles and abstracts, 45 articles were fully assessed for eligibility . Eleven studies (Table ) fulfilled the inclusion and exclusion criteria and were finally included in the present study (PRISMA flow chart shown in Figure ). Two further studies had to be excluded due to the lack of relevant data despite repeated attempts to contact corresponding authors to obtain additional details.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removing of duplicate studies and detailed evaluation of titles and abstracts, 45 articles were fully assessed for eligibility . Eleven studies (Table ) fulfilled the inclusion and exclusion criteria and were finally included in the present study (PRISMA flow chart shown in Figure ). Two further studies had to be excluded due to the lack of relevant data despite repeated attempts to contact corresponding authors to obtain additional details.…”
Section: Resultsmentioning
confidence: 99%
“…These 11 studies comprised a total of 1858 SOT recipients: 1494 (80.4%) liver transplant (LT) recipients, 317 (17.1%) kidney or kidney‐pancreas (KT), recipients and 47 (2.5%) lung transplant (LuT) recipients. Although only one study detailed the ethnicity of the genotyped participants, most patients (87.9% [1634/1858]) came from studies performed in countries with predominant Caucasian populations . All but two studies assessed the impact of polymorphisms in both the promoter and exon 1 regions of the MBL2 gene (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations